Model penguatan loyalitas mahasiswa melalui kualitas pelayanan bimbingan akademik dan kepuasan mahasiswa - Salamatun Asakdiyah; Deny Ismanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This study aims to examine the effect of academic guidance service quality, student satisfaction and the interaction between service quality and student satisfaction in strengthening student loyalty. The sample was determined by convenience sampling and purposive sampling methods. The data was collected by quisioner providing a list of questions to the respondents which contained the quality of service, student satisfaction and student loyalty. The analytical tool used is Moderator Regression Analysis. Meanwhile, to test the hypothesis put forward, the t test and F test are used.. Meanwhile, to find out how much the variables of academic guidance service quality, student satisfaction and the interaction between service quality and student satisfaction were able to explain the student loyalty variables used the coefficient of determination analysis. The results of the partial regression coefficient test with the t test explain that the quality of academic guidance services, student satisfaction and the interaction between service quality and academic guidance with student satisfaction affect student loyalty. Meanwhile, the regression coefficient test simultaneously results that the quality of academic guidance services, student satisfaction and the interaction between the quality of academic guidance services and student satisfaction have an effect on student loyalty.